Digitalization of Employee Performance Appraisal System: Ensuring Fairness and Transparency in Human Resource (HR) Practices in Steel Construction Company - Wirapraja, Alexander; Basatha, Rizky; Manggaetan, Fanny Megawati (Bina Nusantara University, 2025)
Digital transformation in human resource department (HRD) within performance appraisal process is initiated from employee management and supported by the commitment of leaders to create aspects of openness and fairness. In this context, PT. X Surabaya is a steel construction company that still carries out employee performance appraisal process manually, causing problems such as being considered unfair, non-transparent, and inaccurate in the assessment process, as well as frequent delays in the process. This causes feelings of unfairness and suspicion from employees, leading to a negative work atmosphere and impacting productivity and performance. Therefore, this research aims to design employee performance appraisal information system by applying Waterfall model as the development method. The novelty was the integration of human resource (HR) transformation from traditional to digital, by prioritizing the principles of fairness and transparency in the context of employee performance appraisal. This result showed that web-based performance appraisal information system effectively managed the appraisal process digitally, enabling leaders to monitor employee performance and enhance time efficiency. The existence of a system prioritizes transparency and fairness because the assessment process was carried out in two directions, from leaders to employees. Therefore, employee welfare and job satisfaction were improved due to effective and objective assessment.